Organ-saving Operations in Comprehensive Treatment of Lower-Ampullary Rectal Cancer - Uktam Kurbankulov1, Abrorbek Yusupbekov2, Bekhzod Abdullaev3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In recent decades, in many countries of the world there has been an increase in the incidence of colorectalcancer (CRC). The annual occurrence of 50 new cases of colorectal cancer per 100,000 population determinesa 5% population risk of developing the disease throughout life 1. An alarming fact is that for the 100 newlydiagnosed patients with CRC, more than 70 deaths occur, of which, in the 1st year from the moment ofdiagnosis, about 40%. This circumstance is due to the fact that when patients first go to the doctor, advancedforms of CRC (stage III-IV) are diagnosed in 62.4% of patients. In 25-30% of patients, distant metastasesare detected at the time of surgery. In recent years, there has been a tendency to expand indications fororgan-preserving operations in the CRC.At the same time, it is necessary to formulate clear criteria fortheir implementation on the basis of a comparative analysis of long-term treatment results, the frequencyof local regional relapses, the development and implementation of techniques using staplers, as well asthe justification of indications for the use of combined and complex treatment programs that increase theradicalism and ablasticity of surgical interventions.